PENGARUH INDEKS KEBERLANJUTAN PERKEBUNAN KELAPA SAWIT TERHADAP PENDAPATAN MASYARAKAT SEKITAR DI KALIMANTAN TENGAH - Yuprin, A. D.; Agus Yuniawan Isyanto (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2018)
This study aims to analyze the influence of the sustainability index of palm oil plantations along with other factors on the income of the local community in Central Kalimantan. The research sample was oil palm plantation companies which were purposively selected based on the watershed area and the sample of the local communities were randomly selected in the ring one region group. Data were analyzed using multiple linear regression equations with the dependent variable, namely income and independent variables, namely the age of the family head, the education of the family head, the number of family members, the number of income sources and the sustainability index of the oil palm plantation companies. The results showed that age, education and sustainability index of palm oil plantation companies had a positive and significant effect on household income levels of local community, while the number of household members and the number of sources of income did not significantly influence the level of household income level. Significant influence of the sustainability index of palm oil plantation companies on household income levels indicates that the higher the sustainability index of the palm oil plantation, the higher the income of local communities